Apelin levels are higher in obese patients with endometrial cancer. Issue 2 (27th August 2014) - Altinkaya, S. Ozlem; Nergiz, Sümeyra; Küçük, Mert; Yüksel, Hasan
Abstract Aim The aim of the present study was to evaluate serum concentrations of apelin, a newly discovered adipocytokine, in relation with tumor markers, metabolic profile and clinicopathologic features of patients with endometrial cancer. Material and Methods A total of 46 women with endometrial cancer and 44 controls were eligible for the study. Clinicopathologic features and metabolic profile as well as apelin‐36 levels were evaluated in each subject. Results Women with endometrial cancer exhibited higher serum concentrations of apelin levels than controls (215.1 ± 59.8 pg/mL vs 177.3 ± 55.2 pg/mL, P = 0.002). Apelin levels were significantly correlated positively with body mass index, fasting insulin levels and homeostasis model assessment index (P < 0.05). When patients were further divided into obese (body mass index ≥ 30) and non‐obese women, apelin levels remained higher in women with endometrial cancer in the obese group (P = 0.006, 243.5 ± 49.2 pg/mL vs 200.5 ± 52.7 pg/mL, respectively); whereas these levels were similar in the non‐obese group (P = 0.879, 161.9 ± 37.5 pg/mL vs 159.6 ± 51.3, respectively). After adjustment for all possible confounding factors, age, apelin levels > 160 pg/mL, and diabetes mellitus were found to be associated with risk of endometrial cancer. Conclusion The data of the present study suggest that higher levels of circulating apelin are associated with an increased risk of developing endometrial cancer in obese women.